Gestational Diabetes Mellitus-Associated Hyperglycemia Impairs Glucose Transporter 3 Trafficking in Trophoblasts Through the Downregulation of AMP-Activated Protein Kinase - Zhang, Li; Yu, Xinyang; Wu, Yue; Fu, Huijia; Xu, Ping; Zheng, Yangxi; Wen, Li; Yang, Xiaotao; Zhang, Fumei; Hu, Mingyu; Wang, Hao; Liu, Xiyao; et al. (Frontiers in Cell and Developmental Biology, 2021)
AMP-activated protein kinase (AMPK) is an important regulator of glucose metabolism, and glucose transporter 3 (GLUT3) is an efficient glucose transporter in trophoblasts. Whether placental AMPK and GLUT3 respond accordingly to gestational diabetes mellitus (GDM) remains uncertain. Here, we explored the regulatory role of AMPK in the GLUT3-dependent uptake of glucose by placental trophoblasts and the viability of the cells. In this study, the level of glycolysis in normal and GDM-complicated placentas was assessed by LC-MS/MS. The trophoblast hyperglycemia model was induced by the incubation of HTR8/SVneo cells with a high glucose concentration. GDM animal models were generated with db/ + mice and C57BL/6J mice fed a high-fat diet, and AMPK was manipulated by the oral administration of metformin. The uptake of glucose by trophoblasts was assessed using 2-NBDG or 2-deoxy-D-[3H] glucose. The results showed that GDM is associated with impaired glycolysis, AMPK activity, GLUT3 expression in the plasma membrane (PM) and cell survival in the placenta. Hyperglycemia induced similar changes in trophoblasts, and these changes were rescued by AMPK activation. Both hyperglycemic db/ + and high-fat diet-induced GDM mice exhibited a compromised AMPK–GLUT3 axis and suppressed cell viability in the placenta as well as excessive fetal growth, and all of these effects were partially alleviated by metformin. Taken together, our findings support the notion that AMPK activation upregulates trophoblast glucose uptake by stimulating GLUT3 translocation, which is beneficial for viability. Thus, the modulation of glucose metabolism in trophoblasts by targeting AMPK might ameliorate the adverse intrauterine environment caused by GDM.